General practitioners' views and experiences in caring for patients after sepsis: a qualitative interview study. Issue 2 (10th February 2021) - Gehrke-Beck, Sabine; Gensichen, Jochen; Turner, Katrina M; Heintze, Christoph; Schmidt, Konrad FR
Abstract : Background: Patients surviving critical illnesses, such as sepsis, often suffer from long-term complications. After discharge from hospital, most patients are treated in primary care. Little is known how general practitioners (GPs) perform critical illness aftercare and how it can be improved. Within a randomised controlled trial, an outreach training programme has been developed and applied. Objectives: The aim of this study is to describe GPs' views and experiences of caring for postsepsis patients and of participating a specific outreach training. Design: Semistructured qualitative interviews. Setting: 14 primary care practices in the metropolitan area of Berlin, Germany. Participants: 14 GPs who had participated in a structured sepsis aftercare programme in primary care. Results: Themes identified in sepsis aftercare were: continuity of care and good relationship with patients, GP's experiences during their patient's critical illness and impact of persisting symptoms. An outreach education as part of the intervention was considered by the GPs to be acceptable, helpful to improve knowledge of the management of postintensive care complications and useful for sepsis aftercare in daily practice. Conclusions: GPs provide continuity of care to patients surviving sepsis. Better communication at the intensive care unit–GP interface and training in management of long-term complications of sepsis may be helpful to improve sepsis aftercare. Trial registration number: ISRCTN61744782 .